Kajian Implikasi Undang-undang Cipta Kerja Terhadap Peraturan Daerah Tentang Bangunan Gedung di Kabupaten Wonogiri - Nurokhman, Nurokhman; Wibowo, Richo Andi; Saputra, Ashar; Hariyanto, Gatot (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This research aims to identify the readiness of the Wonogiri Regency in 2021 regarding regional policies in building planning that support the Job Creation Law (No. 11/2020). Several analytical approaches are used with data taken directly through interviews and focus group discussions and other supporting data. As a result, Wonogiri Regency has two options, namely first, the Wonogiri Regency Building Regulations are revoked in their entirety on the grounds that the "spirit" has been amended by Law Number 11/2020 and PP Number 16/2021 concerning Building Implementation Regulations whose regulatory concept has changed from IMB to PBG . The second option is partial revision. In its implementation, it is necessary to increase the effectiveness of law enforcement, SIMBG tools and increase the capacity and competence of human resources as well as ensuring the Regional Regulations on RTRW and RDTR, and the Regional Regulation on Retributions.